ANALISIS KEMAMPUAN KONEKSI DAN KOMUNIKASI MATEMATIS DITINJAU DARI KEPERCAYAAN DIRI SISWA SMP - Nurul, Nurul; Octaviani, Ati; Zanthy, Luvy Sylviana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
AbstractThe purpose of this study was to analyze the mathematical connection ability of the students of Pasundan Middle School 1 Cimahi class VII-D in the school year 2018-2019. The subjects taken were 9 students with category 3 high-ability students, 3 moderate-capable students, and 3 low-ability students. The approach used in accordance with the 2013 curriculum is a scientific approach with discovery learning models. Data obtained from the results of student answers. The process of data analysis is the process of answering students on each question that measures indicators of students' mathematical communication skills. The process of data analysis is the process of answering students on each question that measures indicators of students' mathematical connection abilities. From the results of the study, it was found that high-ability students could master three indicators, namely using inter-collaborative mathematical relationships, using interrelationships between mathematical topics and topics outside mathematics, understanding equivalent representations of the same concepts. Students who are capable of mastering two indicators, namely using relationships between topics, understanding equivalent representations of the same concept. Low-ability students master an indicator that is understanding equivalent representations of the same concept. From the results of the study, it was found that high-ability students can master three indicators namely connecting images to mathematical ideas, expressing daily events in language or mathematical symbols and explaining the idea of situations and mathematical relations with images. Students who are capable of mastering two indicators namely connecting images into mathematical ideas, expressing daily events in language or mathematical symbols and explaining the idea of the situation. Low-ability students only master one indicator which is connecting images into mathematical ideas. On an attitude scale, students have high self-esteem. This can be viewed from the responses of students who respond more positively.Keywords: Connection Ability, Communication Ability, Self ConfidenceAbstrakTujuan Penelitian ini adalah untuk menganalisis kemampuan koneksi matematis siswa SMP Pasundan 1 Cimahi kelas VII-D tahun pelajaran 2018-2019. Subjek yang diambil berjumlah 9 orang siswa dengan kategori 3 siswa berkemampuan tinggi, 3 siswa berkemampuan sedang, dan 3 siswa berkemampuan rendah. Pendekatan yang digunakan sesuai dengan kurikulum 2013 yaitu pendekatan saintifik dengan model pembelajaran discovery learning. Data diperoleh dari hasil jawaban siswa. Proses analisis data yaitu proses jawaban siswa pada setiap soal yang mengukur indikator kemampuan komunikasi matematis siswa. Proses analisis data yaitu proses jawaban siswa pada setiap soal yang mengukur indikator kemampuan koneksi matematis siswa. Dari hasil penelitian diperoleh bahwa siswa yang berkemampuan tinggi dapat menguasai tiga indikator yaitu menggunakan hubungan antartopik matematika, menggunakan keterkaitan antar topik matematika dengan topik diluar matematika, memahami representasi ekuivalen konsep yang sama. Siswa berkemampuan sedang menguasai dua indikator yaitu menggunakan hubungan antar topik, memahami representasi ekuivalen konsep yang sama. Siswa berkemampuan rendah menguasai satu indikator yaitu memahami representasi ekuivalen konsep yang sama. Dari hasil penelitian diperoleh bahwa siswa yang berkemampuan tinggi dapat menguasai tiga indikator yaitu menghubungkan gambar ke dalam idea matematika, menyatakan peristiwa sehari-hari dalam bahasa atau symbol matematika dan menjelaskan idea situasi dan relasi matematik dengan gambar. Siswa berkemampuan sedang menguasai dua indikator yaitu menghubungkan gambar kedalam idea matematika, menyatakan peristiwa sehari-hari dalam bahasa atau symbol matematika dan menjelaskan idea situasi . Siswa berkemampuan rendah hanya menguasai satu indikator yaitu menghubungkan gambar kedalam idea matematika. Pada skala sikap, siswa memiliki rasa percaya diri yang tinggi. Hal ini dapat ditinjau dari respon siswa yang lebih banyak merespon positif.Kata Kunci: Kemampuan Koneksi, Kemampuan Komunikasi, Kepercayaan Diri